In Vitro Evaluation of Biofield Treatment on Cancer Biomarkers Involved in Endometrial and Prostate Cancer Cell Lines - Trivedi, Mahendra Kumar; Harish Shettigar, Shrikant Patil; Snehasis Jana, Mayank Gangwar (Journal of cancer science & therapy, 2015)
Increasing cancer rates particularly in the developed world are associated with related lifestyle and environmental exposures. Combined immunotherapy and targeted therapies are the main treatment approaches in advanced and recurrent cancer. An alternate approach, energy medicine is increasingly used in life threatening problems to promote human wellness. This study aimed to investigate the effect of biofield treatment on cancer biomarkers involved in human endometrium and prostate cancer cell lines. Each cancer cell lines were taken in two sealed tubes i.e. one tube was considered as control and another tube was subjected to Mr. Trivedi’s biofield treatment, referred as treated. Control and treated samples were studied for the determination of cancer biomarkers such as multifunctional cytokines viz. interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), interleukin-2 receptor (IL-2R), prostate specific antigen (PSA), and free prostate specific antigen (FPSA) concentrations using ELISA assay on day 10. Experimental results showed a significant reduction of IL-6 level in endometrium (12%) and prostate (98.8%) cancer cell lines while a significant increase was observed in TNF-α level in endometrium (385%) and prostate (89.8%) cancer cell lines as compared to control. No alteration of PSA level was observed in biofield treated endometrium and prostate cell line. Similarly, no alterations were evident in IL-2R and FPSA levels in endometrium and prostate cell lines after biofield treatment as compared to control. In conclusion, results suggest that biofield treatment has shown significant alterations in the level of cytokines (IL-6 and TNF-α) in both endometrium and prostate cancer cell lines.